2021
DOI: 10.15252/emmm.202013110
|View full text |Cite
|
Sign up to set email alerts
|

uPA‐PAI‐1 heteromerization promotes breast cancer progression by attracting tumorigenic neutrophils

Abstract: High intratumoral levels of urokinase-type plasminogen activator (uPA)-plasminogen activator inhibitor-1 (PAI-1) heteromers predict impaired survival and treatment response in early breast cancer. The pathogenetic role of this protein complex remains obscure. Here, we demonstrate that heteromerization of uPA and PAI-1 multiplies the potential of the single proteins to attract protumorigenic neutrophils. To this end, tumor-released uPA-PAI-1 utilizes very low-density lipoprotein receptor and mitogen-activated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…M1 and M2 macrophages are considered antitumor and protumor, respectively ( 34 ). Neutrophils have also been shown to have cancer-promoting effects ( 35 , 36 ). However, we did not observe any influence of myeloid leukocyte depletion on tumor growth in the CDX model (fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…M1 and M2 macrophages are considered antitumor and protumor, respectively ( 34 ). Neutrophils have also been shown to have cancer-promoting effects ( 35 , 36 ). However, we did not observe any influence of myeloid leukocyte depletion on tumor growth in the CDX model (fig.…”
Section: Resultsmentioning
confidence: 99%
“…Myeloid leukocytes play important and complex roles in cancer development ( 34 , 36 ). A recent study showed that heteromerization of uPA and plasminogen activator inhibitor-1 (PAI-1), two key components of the uPA-uPAR system, promotes breast cancer progression by attracting tumorigenic neutrophils ( 35 ). In addition, M1 and M2 macrophages are considered to have antitumor and protumor function, respectively ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, pre-incubation with mAb-2E3 was able to block the binding between LRP1-Cluster II-Fc and PAI-1, with the IC50 value of mAb-2E3 was 26.45 nM (Fig. 7B), while the IC50 value of mIgG was 2.96e 25 nM.…”
Section: Mab-2e3 Blocks the Binding Between Lrp1-cluster Ii-fc And Pai-1mentioning
confidence: 95%
“…Vitronectin binds to PAI-1 through the helices hD, hE, and hF in the flexible joint region. LRP1 endocytoses PAI-1 or PAI-1-/uPA/tPA mainly through recognition with several key residues of helix hD, such as K60, K69, R76 and R138 25 , 26 . In response to this feature, small molecule inhibitors and antibodies targeting PAI-1 have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Blockade of uPA‐PAI‐1 heteromerization by a novel small molecule inhibitor WX‐340 effectively prevents tumor progression. [ 148 ] Wang et al demonstrate that SPI1 (Salmonella pathogenicity island 1) physically interacts with SPIB to promote aerobic glycolysis in colon cancer cells, which induces pro‐tumor polarization of neutrophils and in turn their delivery of SPI1 mRNA into cancer cells, constituting a positive feedback loop to favor cancer progression. [ 149 ] Therapeutic targeting of SPIB‐SPI1 interaction with an inhibitory peptide of 11 amino acids (termed as SIP‐11) inhibits aerobic glycolysis and cancer progression.…”
Section: Targeting Neutrophils For Cancer Therapymentioning
confidence: 99%